Circular economy education approaches to water use in the industrial sector - Khajuria, Anupam; Rajput, Ritika (Frontiers in Environmental Science, 2025)
As global industrial waste demands rise alongside increasing water scarcity, it becomes imperative to adopt circular economy principles within industrial water management. Traditional linear models of resource use have become unsustainable, demanding systemic transitions toward circular, closed-loop approaches. This paper explores the intersection of circular economy education and industrial water uses by examining how circular economy education and practices can transform industrial water use and improve sustainability outcome. Through case studies and best practices, this research illustrates successful implementations of circular water economy principles, demonstrates the implementation of closed-loop water systems, cascading reuse and zero liquid discharge technologies can reduce freshwater intake in industrial applications and emphasises the role of public-private partnerships in promoting water reuse projects. The paper also addresses the challenges and barriers to implementation, focusing on regulatory issues, resource limitations, and gaps in awareness. It concludes by proposing future directions for integrating circular economy principles into industrial water management and offers policy recommendations to foster circular water economy education. Hence, it contributes qualitative analysis to the growing body of knowledge on sustainable water management practices and provides valuable insights for policymakers and industry professionals seeking to advance circular economy approaches in industrial water use.